Ondina Otta Klasinc (1924–2016): Ob stoletnici rojstva (University of Maribor Press, 2024)
Ondina Otta Klasinc (1924–2016): A Centenary After her Birth. With the biographical and memorial publication, the University of Maribor Library pays tribute to the centenary of the birth of the internationally renowned soprano, long-time champion of the Maribor Opera, and full professor Ondina Otta Klasinc (1924–2016). The publication is the seventh in the Personalities collection series. The library is committed to honouring the artist, as it permanently preserves her legacy. Based on her albums Vita artistica di Ondina Otta Klasinc [1946–1963], The Artistic Life of Ondina Otta - Klasinc [1964–2003], and Ondina Otta Klasinc, Marko Košir already published her biography in the Maribor opera stars book in 2013. This text, in which the author skilfully outlines the singer’s artistic image and guides the reader through her rich creativity, is the central part of the publication. The second part illuminates the singer’s personality through the memories of her contemporaries - conductors, musicians, students, and friends Milena Morača, full professor Vlatka Oršanić, Janez Lotrič, Nevenka Verstovšek, Samo Ivačič, Vlasta Doležal Rus, Boris Švara, full professor Simon Robinson, Stane Jurgec, M. A., and Majda Emeršič. The publication also contains a bibliography about Ondina Otta Klasinc.